2006
DOI: 10.1007/s00238-006-0080-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and long-term follow-up after liposuction procedures

Abstract: Liposuction is one of the most common aesthetic procedure used in plastic surgery. Reports are available on the results, the probable complications, and the feedback of patients. However, systematic studies dealing with these aspects using reliable large-enough data are still needed. The data comprised 116 procedures during a 6-year period up to 2005. The data were processed and categories of results were formed. Furthermore, a follow-up examination and a survey on the feedback of patients were carried out. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
1
1
1
Order By: Relevance
“…These same authors also reported, as we did, that UAL did not improve patients' self-perceived productivity and health. Minuscule differences in the rate of satisfaction of our patients and their contentment with body appearance versus previous studies 12,20 can be attributed to demographic differences, including the higher BMI of our study group. In terms of predictive factors, a similar patient survey conducted by Hensel et al 21 revealed that symptom improvement (97% of their patients) and satisfaction (86%) with surgery have a direct relationship to a patient's likelihood to recommend the procedure to a friend (86%).…”
Section: 5) Nscontrasting
confidence: 60%
“…These same authors also reported, as we did, that UAL did not improve patients' self-perceived productivity and health. Minuscule differences in the rate of satisfaction of our patients and their contentment with body appearance versus previous studies 12,20 can be attributed to demographic differences, including the higher BMI of our study group. In terms of predictive factors, a similar patient survey conducted by Hensel et al 21 revealed that symptom improvement (97% of their patients) and satisfaction (86%) with surgery have a direct relationship to a patient's likelihood to recommend the procedure to a friend (86%).…”
Section: 5) Nscontrasting
confidence: 60%
“…Los grandes avances en la tecnología aplicada en el campo de la Cirugía Estética han permitido beneficiar a los pacientes ofreciéndoles menos traumatismo y resultados estéticos naturales (1,2). Siendo la liposucción una técnica que aparece en los años 70, ha sufrido desde entonces varias modificaciones que han optimizado su aplicación, lo que no pone en duda su efectividad (3).…”
Section: Introductionunclassified
“…Major advances in technology applied to aesthetic surgery have allowed us to offer benefits to patients like less trauma and better natural aesthetics results . Liposuction, the [11] Suction assisted lipectomy (SAL) a technique born in the 70's [12,13] has gone through several modifications that have optimized its application thereby casting no doubt on its effectiveness . Laser (with affinity for water) applied to the [14] treatment of lipodystrophy has revolutionized the liposuction technique, offering less surgical trauma for patients which translates into less pain, less blood loss, no hematomas, minimum ecchymosis, less edema and insignificant skin retraction, with a short recovery period and reduced hospital cost .…”
Section: Introductionmentioning
confidence: 99%